Effectiveness of sexual and reproductive health education and attitude in early adolescent in Kuantan, Pahang - Abd. Aziz, Karimah Hanim; Jamani, Nurjasmine Aida; Wan Omar, Wan Nurul Amirah; Zulkefli, Nur Syazwani; Yusni, Anis Hazwanie (2018)
Sexual reproductive health (SRH) is an increasingly crucial component in global health development. Lack of knowledge and attitude towards sexual and reproductive health among adolescents is one of factors that lead to increase in premarity sexual activity nowadays. Preventive measures based on education and intervention program should be taken in order to tackle this problem